Un ejemplo de renovación pedagógica de las enseñanzas científicas universitarias a escala internacional - Gomel, M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this article three strategies, complementary to the renewing of Universíty scientific teaching, are briefly described; and some specific samples of the results obtained in Chemistry are presented.